Inklusi Keuangan dan Stabilitas Sistem Keuangan (Bank Z-Score) di Asia - Fauziah Fauziah; Ayu Febriyanti; Nurul Hidayatin Nisa (Fakultas Ekonomi Universitas Islam 45, 2020)
In the last two decades, there were two crises in Asia. This incident reminded the importance of maintaining financial system stability. This research aims to discover the effect of financial inclusion on financial system stability. Financial inclusion is proxied with the Financial Inclusion Index (IFI); financial system stability is proxied with bank Z-score. This study using the 2009-2018 annual data from 10 developing countries in Asia, i.e. Afghanistan, Bangladesh, Brunei Darussalam, India, Indonesia, Malaysia, Pakistan, the Philippines, Singapore and Thailand. The Generalized Method of Moments (GMM) results shows that financial inclusion negatively affects financial system stability. Increasing financial inclusion causes financial system instability. Financial inclusion is approved through rapid credit growth or fund intermediation that isn’t accompanied by agreements that can adversely affect finances